Slovak Realia in the Czech Translation of the Novel The House of the Deaf Man by Peter Krištúfek in Contrast to its English Translation - Kniazkova, Viktoria (Bohemistyka, 2019)
The article deals with two groups of realia in the Slovak novel by Peter Krištúfek (1973–2018). The first one are those concerning Slovak traditional culture, which are used in a form of theatrical scenery by the author. The second one are those connected with Slovak identity, as the writer understands it. The article offers the comparative analysis of the Slovak text with its translations into Czech and English. The conclusion is made about different translators’ strategies according to the translation purpose and extralinguistic circumstances and the necessity of the Czech translations of Slovak fiction despite the unique closeness of these two Slavic languages.